Enhanced US/CT/MR imaging of integrin αvβ3 for liver fibrosis staging in rat - Tang, Xueyao; Li, Xuan; Li, Mingxing; Zhong, Xiaoling; Fu, Wenguang; Ao, Meng; Xuan, Jiqing (Frontiers in Chemistry, 2022)
Liver fibrosis is a global health challenge with high morbidity and mortality rates, and diagnostic sensitivity of liver fibrosis tests can be increased using multimodal molecular agents. We designed cyclic arginine-glycine-aspartic acid (cRGD)-modified nanoparticles (NPs) using ultrasound (US)/computed tomography (CT)/magnetic resonance (MR) triple-modality imaging to evaluate liver fibrosis stages. In vitro and in vivo studies were conducted using primary hepatic stellate cells (HSCs) and a rat model of liver fibrosis induced by carbon tetrachloride (CCl4). Our results showed cRGD-poly(lactic-co-glycolic acid)-Fe3O4-perfluorocarbon bromide (cRGD-PLGA-Fe3O4-PFOB) NPs were preferentially internalised by activated HSCs (aHSCs). The main cell types expressing integrin αvβ3 during liver fibrogenesis were the aHSCs. The protein levels of αv and β3 expressed on aHSCs increased with the progression of liver fibrosis. After intravenous injection of cRGD-PLGA-Fe3O4-PFOB NPs, the echo intensity (EI) values, CT values, and T2 values of liver parenchyma correlated well with liver fibrosis severity. cRGD-PLGA-Fe3O4-PFOB NPs as multifunction contrast agents showed great potential to reflect the degree of HSC activation and distinguish among different liver fibrotic stages. The ligand-directed and integrin αvβ3-mediated accumulation provides active and passive targeting capabilities, permitting the targeted multimodal imaging of cRGD-PLGA-Fe3O4-PFOB NPs, which delivers accurate non-invasive diagnosis and real-time monitoring of liver fibrosis development.